Fiqih Wanita: Sebuah Tinjauan Historis - M Harir Muzakki (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to examine the development of women's fiqh (Islamic jurisprudence) in a historical perspective and how social and cultural dynamics influence the understanding of Islamic law related to women. The method used is qualitative with a historical-analytical approach, through a literature review of classical fiqh books and contemporary works. The results show that women's fiqh developed in various schools of thought with diverse interpretations, often influenced by the social context of the time. In some periods, women's fiqh was more restrictive, while in the modern context, more inclusive and gender-justice oriented reinterpretations emerged. This study emphasizes that women's fiqh is dynamic and needs to be contextualized according to the principle of maqashid sharia in order to remain relevant to the needs of Muslim women in the contemporary era.